2018
DOI: 10.1016/j.jcf.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Variability of lung clearance index in clinically stable cystic fibrosis lung disease in school age children

Abstract: LCI within-subject variability was low and comparable to FEV% pred. which strengthen the use of LCI to monitor lung disease progression in CF patients. An increase in LCI >17% compared to previous LCI-measurement in clinically stable CF patients may therefore indicate early lung disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 31 publications
5
38
1
1
Order By: Relevance
“…year. 86 Measures done during periods of clinical stability showed low within-subject variability; an increase in LCI > 17% was the upper limit of normal variability in this cohort. These studies add to the understanding of variability between subjects, over time and with different assessment systems.…”
Section: Multiple Breath Washoutmentioning
confidence: 59%
See 1 more Smart Citation
“…year. 86 Measures done during periods of clinical stability showed low within-subject variability; an increase in LCI > 17% was the upper limit of normal variability in this cohort. These studies add to the understanding of variability between subjects, over time and with different assessment systems.…”
Section: Multiple Breath Washoutmentioning
confidence: 59%
“…During the study, systematic difference between two commonly used commercial software systems were not seen, indicating that they could be used interchangeably for both research and for disease monitoring. A second study examining variability of LCI was also assessed in 25 children with CF who performed N 2 MBW and spirometry every 3 months for 1 year . Measures done during periods of clinical stability showed low within‐subject variability; an increase in LCI > 17% was the upper limit of normal variability in this cohort.…”
Section: Physiological Assessmentmentioning
confidence: 99%
“…There is increasing evidence on the clinical utility of LCI. In addition to LCI being used as a clinical endpoint [5,15], it has also been used to assess mucociliary clearance in young children [20] treated with CFTR-modulators [15] and to monitor disease progression [21], or both [22]. However, this study with inhaled tobramycin demonstrated that changes in LCI, FEV 1 and CFU at week 1, 4 and 8 were not statistically significant.…”
Section: Discussionmentioning
confidence: 88%
“…There is increasing evidence on the clinical utility of LCI. In addition to LCI being used as a clinical endpoint [5,15], it has also been used to assess mucociliary clearance in young children [17] treated with CFTR-modulators [15] and to monitor disease progression [18], or both [19]. However, this study with inhaled tobramycin demonstrated that changes in LCI, FEV 1 and CFU at week 1, 4 and 8 were not statistically significant.…”
Section: Discussionmentioning
confidence: 88%